Multimedia in developing communicative competence among ESL students: cultural aspect - Badan, A. A.; Nedainova, I. V.; Akopiants, N. M. (Херсонський державний університет, 2018)
This article presents the results of the use of multimedia tools in the development of communicative competencies in terms of enhancing the cultural aspect in the process of teaching English to students who study it as a foreign language. Special attention is paid to the consideration of specific examples of the use of multimedia by teachers of the department of business foreign language and translation of the National Technical University "Kharkiv Polytechnic Institute".

Стаття присвячена застосуванню мультимедійних технологій в процесі розвитку комунікативної компетентності серед студентів, які вивчають англійську мову як іноземну, з точки зору культурного аспекту. Автори статті розглядають історичні передумови виникнення такого поняття як мультимедія, аналізують етапи його розвитку, виділяють місце в сучасній педагогіці, а також відзначають його значення у сучасній методології навчання та викладання іноземної мови.
Keywords: multimedia technologies; communicative competence; cultural aspect; learner-centered approach; ESL students; мультимедійні технології; комунікативна компетенція; культурологічний аспект; особистісно-орієнтований підхід